Language Proficiency and Academic Integration: Analyzing the Needs of University of Debrecen Staff - Edina VÁRNAGY (Cross-Cultural Management Journal)
This study aims to examine the language challenges faced by local and international university staff at the University of Debrecen. Utilizing a mixed-methods approach, a questionnaire was distributed to local colleagues to gather insights into their language-related experiences, while interviews were conducted with international colleagues to capture their unique perspectives. The findings reveal a significant demand for language courses among the university's employees. Notably, international colleagues who had access to Hungarian language courses, especially those offered by their respective faculties, demonstrated better language proficiency and overall performance. These results emphasize the critical need for comprehensive language support programs to improve the academic and professional integration of both local and international staff.